A Sentinel in the Crosstalk Between the Nervous and Immune System: The (Immuno)-Proteasome - Limanaqi, Fiona; Biagioni, Francesca; Gaglione, Anderson; Busceti, Carla Letizia; Fornai, Francesco (Frontiers in Immunology, 2019)
The wealth of recent evidence about a bi-directional communication between nerve- and immune- cells revolutionized the traditional concept about the brain as an “immune-privileged” organ while opening novel avenues in the pathophysiology of CNS disorders. In fact, altered communication between the immune and nervous system is emerging as a common hallmark in neuro-developmental, neurodegenerative, and neuro-immunological diseases. At molecular level, the ubiquitin proteasome machinery operates as a sentinel at the crossroad between the immune system and brain. In fact, the standard proteasome and its alternative/inducible counterpart, the immunoproteasome, operate dynamically and coordinately in both nerve- and immune- cells to modulate neurotransmission, oxidative/inflammatory stress response, and immunity. When dysregulations of the proteasome system occur, altered amounts of standard- vs. immune-proteasome subtypes translate into altered communication between neurons, glia, and immune cells. This contributes to neuro-inflammatory pathology in a variety of neurological disorders encompassing Parkinson's, Alzheimer's, and Huntingtin's diseases, brain trauma, epilepsy, and Multiple Sclerosis. In the present review, we analyze those proteasome-dependent molecular interactions which sustain communication between neurons, glia, and brain circulating T-lymphocytes both in baseline and pathological conditions. The evidence here discussed converges in that upregulation of immunoproteasome to the detriment of the standard proteasome, is commonly implicated in the inflammatory- and immune- biology of neurodegeneration. These concepts may foster additional studies investigating the role of immunoproteasome as a potential target in neurodegenerative and neuro-immunological disorders.